MODEL PEMBERDAYAAN MASYARAKAT MELALUI INTEGRASI TRI HITA KARANA DALAM WISATA SPIRITUAL BERKELANJUTAN DI DESA PENATIH DANGIN PURI - Kadek Agustina Cahyani; Ni Nyoman Sundarianti; A A Istri Mas Deny Ernawati; I Ketut Parikesit; Ni Luh Putu Margayawati; Budi Wiyono; Ni Putu Tirka Widanti; Nyoman Sudiyani; Ni Made Anggia Paramesthi Fajar (LPPM Institut Pendidikan Nusantara Global, 2025)
Pengabdian Kepada Masyarakat (PKM) was carried out in Penatih Dangin Puri Village, East Denpasar, Bali, with the aim of developing a community empowerment model based on Tri Hita Karana in managing sustainable spiritual tourism. The village has six tourism potentials, namely spiritual tourism (temples and griya), Ashitaba tourism, sports tourism, nature/subak tourism, recreational tourism, and local MSME development. Based on the results of surveys, observations, participation in traditional ceremonies, and Focus Group Discussions (FGD), spiritual tourism was determined as the main basis for village development due to its religious, social, and ecological values. The integration of Tri Hita Karana has proven to be a strong foundation in tourism development: Parahyangan through the strengthening of sacred temples and rituals; Pawongan through community, youth, and MSME involvement; and Palemahan through the preservation of the village environment. The PKM activities also revealed that community empowerment is the key factor, where traditional leaders, religious leaders, youth, and local MSMEs actively participated in designing a tourism model based on local wisdom. The findings of this PKM confirm that spiritual tourism grounded in Tri Hita Karana can serve as a best practice model in creating authentic, sustainable village tourism while enhancing community welfare.